2014
DOI: 10.1038/nature13664
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-evoked LTP driven by dendritic plateau potentials in vivo

Abstract: Long-term synaptic potentiation (LTP) is thought to be a key process in cortical synaptic network plasticity and memory formation. Hebbian forms of LTP depend on strong postsynaptic depolarization, which in many models is generated by action potentials that propagate back from the soma into dendrites. However, local dendritic depolarization has been shown to mediate these forms of LTP as well. As pyramidal cells in supragranular layers of the somatosensory cortex spike infrequently, it is unclear which of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
267
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(319 citation statements)
references
References 40 publications
37
267
2
Order By: Relevance
“…Given that dendritic spikes are normally suppressed by strong feedforward inhibition(9), the ability of the LRIPs to enhance dendritic spiking during a precise temporal window may contribute to the dendritic spike firing in vivo observed during behaviorally relevant cooperative activity(39). The LRIP-dependent dendritic spikes are likely to participate in the induction of ITDP and the fine-tuning of learning and memory, based on the role of such spikes in both other forms of Ca 2+ -dependent synaptic plasticity(35, 36, 40) and non-linear gain modulation during associative learning(35) and sensory tuning(41). …”
Section: Discussionmentioning
confidence: 99%
“…Given that dendritic spikes are normally suppressed by strong feedforward inhibition(9), the ability of the LRIPs to enhance dendritic spiking during a precise temporal window may contribute to the dendritic spike firing in vivo observed during behaviorally relevant cooperative activity(39). The LRIP-dependent dendritic spikes are likely to participate in the induction of ITDP and the fine-tuning of learning and memory, based on the role of such spikes in both other forms of Ca 2+ -dependent synaptic plasticity(35, 36, 40) and non-linear gain modulation during associative learning(35) and sensory tuning(41). …”
Section: Discussionmentioning
confidence: 99%
“…The increased sensitivity to touch in M1P neurons persisted post-training and could be a result of a strengthening or disinhibition of feedforward responses in S1 (refs. [25][26][27][28][29]. During this period the session-to-session response variability of M1P neurons was reduced compared to baseline conditions, suggesting that sensory representation in these neurons was stabilized.…”
Section: Discussionmentioning
confidence: 79%
“…This fine-scale organization of synaptic inputs had been previously predicted by theoretical studies proposing that synaptic clustering can boost the computational power of a neuron, because it would allow parallel information processing by supra-linear integration of synchronized synaptic inputs in individual dendritic units (Poirazi and Mel, 2001). Since these early predictions, it has been found that supra-linear integration is required for high-level sensory processing (Lavzin et al, 2012;Palmer et al, 2014;Smith et al, 2013) and synaptic plasticity in vivo (Cichon and Gan, 2015;Gambino et al, 2014). Therefore, the clustering of co-active inputs by spontaneous activity could provide the basis for future sensory processing by enabling supra-linear integration.…”
Section: Introductionmentioning
confidence: 86%